Characterization of multidrug-resistant Salmonella enterica serovars Indiana and Enteritidis from chickens in Eastern China. - Yan Lu; Hongyu Zhao; Jian Sun; Yuqi Liu; Xuping Zhou; Ross C Beier; Guojuan Wu; Xiaolin Hou (PLoS ONE, 2014)
A total of 310 Salmonella isolates were isolated from 6 broiler farms in Eastern China, serotyped according to the Kauffmann-White classification. All isolates were examined for susceptibility to 17 commonly used antimicrobial agents, representative isolates were examined for resistance genes and class I integrons using PCR technology. Clonality was determined by pulsed-field gel electrophoresis (PFGE). There were two serotypes detected in the 310 Salmonella strains, which included 133 Salmonella enterica serovar Indiana isolates and 177 Salmonella enterica serovar Enteritidis isolates. Antimicrobial sensitivity results showed that the isolates were generally resistant to sulfamethoxazole, ampicillin, tetracycline, doxycycline and trimethoprim, and 95% of the isolates sensitive to amikacin and polymyxin. Among all Salmonella enterica serovar Indiana isolates, 108 (81.2%) possessed the blaTEM, floR, tetA, strA and aac (6')-Ib-cr resistance genes. The detected carriage rate of class 1 integrons was 66.5% (206/310), with 6 strains carrying gene integron cassette dfr17-aadA5. The increasing frequency of multidrug resistance rate in Salmonella was associated with increasing prevalence of int1 genes (rs = 0.938, P = 0.00039). The int1, blaTEM, floR, tetA, strA and aac (6')-Ib-cr positive Salmonella enterica serovar Indiana isolates showed five major patterns as determined by PFGE. Most isolates exhibited the common PFGE patterns found from the chicken farms, suggesting that many multidrug-resistant isolates of Salmonella enterica serovar Indiana prevailed in these sources. Some isolates with similar antimicrobial resistance patterns represented a variety of Salmonella enterica serovar Indiana genotypes, and were derived from a different clone.